Measuring Economic Journals' Citation Efficiency: A Data Envelopment Analysis Approach - George Emm. Halkos; Nickolaos G. Tzeremes (Economics and Econometrics Research Institute (EERI), 2011)
This paper by using Data Envelopment Analysis (DEA) and statistical inference evaluates the citation performance of 229 economic journals. The paper categorizes the journals into four main categories (A to D) based on their efficiency levels. The results are then compared to the 27 “core economic journals” as introduced by Dimond (1989). The results reveal that after more than twenty years Diamonds' list of “core economic journals” is still valid. Finally, for the first time the paper uses data from four well-known databases (SSCI, Scopus, RePEc, Econlit) and two quality ranking reports (Kiel Institute internals ranking and ABS quality ranking report) in a DEA setting and in order to derive the ranking of 229 economic journals. The ten economic journals with the highest citation performance are Journal of Political Economy, Econometrica, Quarterly Journal of Economics, Journal of Financial Economics, Journal of Economic Literature, American Economic Review, Review of Economic Studies, Journal of Econometrics, Journal of Finance, Brookings Papers on Economic Activity.
Keywords: C02; C14; C61; C67; 330; Ranking journals; Data Envelopment Analysis; Indexing techniques; Nonparametric analysis